Ion Channels of Nociception - Giniatullin, Rashid (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The Special Issue "Ion Channels of Nociception" contains 13 articles united by a focus on the peripheral mechanisms of pain. The content covers the mechanisms of neuropathic, inflammatory, and dental pain as well as pain in migraine and diabetes; nociceptive roles of P2X3, ASIC, Piezo and TRP channels; pain control through GPCRs and pharmacological agents; and nonpharmacological treatment with electroacupuncture.